2016
DOI: 10.1177/2050312116652567
|View full text |Cite
|
Sign up to set email alerts
|

Support for immigration reduction and physician distrust in the United States

Abstract: Objectives:Health research indicates that physician trust in the United States has declined over the last 50 years. Paralleling this trend is a decline in social capital, with researchers finding a negative relationship between immigration-based diversity and social capital. This article examines whether physician distrust is also tied to immigration-based diversity and declining social capital.Methods:Data come from the 2012 General Social Survey, one of the gold standards of US public opinion surveys, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There is a plethora of literature on the challenges of recruitment and retention of ethnic-racial minorities into health research. Immigrants and African Americans have heard of or had negative experiences with the healthcare system, and some have shown a distrust of healthcare professionals ( 19 , 20 ). African American males, across all age groups, reported a lack of trust as a primary reason for their unwillingness to participate in health research ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is a plethora of literature on the challenges of recruitment and retention of ethnic-racial minorities into health research. Immigrants and African Americans have heard of or had negative experiences with the healthcare system, and some have shown a distrust of healthcare professionals ( 19 , 20 ). African American males, across all age groups, reported a lack of trust as a primary reason for their unwillingness to participate in health research ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, trust in science may also be related to perceptions of immigration policies. For instance, distrust in clinicians and practitioners has been associated with support for reducing immigration in the United States (Samson, 2016). Several studies also indicated that people higher on generalized trust reported more positive attitudes towards immigration policies (Macdonald, 2021; Sipinen et al, 2020; van der Linden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%